Effects of Isotricha, Dasytricha, Entodinium, and total fauna on ruminal fermentation and duodenal flow in wethers fed different diets - Ivan, Michael; Neill, L.; Forster, Robert J.; Alimon, Abdul Razak; Rode, Lyle M.; Entz, Toby (Elsevier, 2000)
The objective was to measure rumen fermentation and duodenal flow of amino acids and nonammonia N components in five groups of five ruminally and duodenally cannulated wethers that were fauna-free, or inoculated with the ciliate protozoa genera of Isotricha, Dasytricha, Entodinium, or a normal population (total) of fauna. They were used in two 25-d periods and fed a haycrop-based diet in the first period and a corn silage-based diet in the second period. Feces, duodenal digesta, and rumen contents were sampled in each period and analyzed. The number of Entodinium in wethers containing the Entodinium monofauna was higher than the total protozoa numbers, including Entodinium, in wethers containing total fauna population. The type of diet or fauna did not affect total volatile fatty acid concentrations in rumen fluid. The ammonia N concentration in rumen fluid was higher in wethers containing total fauna (25 mg/100 ml) than in fauna-free wethers fed the two diets (18 and 12 mg/100 ml). In comparison with the respective fauna-free wethers, the concentration of ammonia in wethers containing Entodinium was higher when fed the corn silage diet, but not different when fed the haycrop diet. Ruminal presence of total fauna or Entodinium decreased the nonammonia N by 16 and 17%, and total amino acid flows from the stomach by 20 and 19%, respectively. Flow of bacteria Nwas decreased in wethers fed the two diets when Entodinium or total fauna were present in the rumen. The presence of Isotricha resulted in higher flow of bacteria N in wethers fed the haycrop diet, but the presence of Dasytricha resulted in higher bacteria N flow in wethers fed the corn silage diet. Entodinium was the most detrimental of ciliate protozoa species concerning protein nutrition of the host ruminant.